High fat diet-induced loss of pituitary plasticity in aging female mice with ablated leptin signaling in somatotropes - Miles, Tiffany K.; Odle, Angela K.; Byrum, Stephanie D.; Lagasse, Alex N.; Haney, Anessa C.; Ortega, Victoria G.; Herdman, Ashley K.; MacNicol, Melanie C.; MacNicol, Angus M.; Childs, Gwen V. (Frontiers in Endocrinology, 2025)
IntroductionSomatotropes lacking leptin receptors (LEPR) produce less growth hormone and are poorly responsive to growth hormone releasing hormone (GHRH). Transcriptomic analysis reveals that the mutant somatotropes contain progenitor cell markers (Sox9+) and multiple pituitary hormone transcripts-(Pomc, Prl, Lhb, Tshb and Cga), suggesting that the cells are progenitor cells. The resulting GH deficiency contributes to adult-onset obesity in the mutant, due to an increase in abdominal fat.ObjectivesThis study examined how a high-fat diet (HFD) affected pituitary transcriptomic function in older (10-month) female mutants lacking leptin receptors (LEPR) in somatotropes and intact littermate controls. We hypothesized that pituitary cells from both the older control females and the female mutants would be greatly affected by the oxidative stress from the HFD.MethodsMice were exposed to a 60% HFD for 16 weeks, followed by glucose tolerance testing and 3-day monitoring in metabolic cages (CLAMS). Pituitaries were harvested, cells dispersed and subjected to single cell-RNA-seq (scRNA-seq) with bioinformatic analysis. Serum was collected and analyzed for pituitary hormones and cytokines.ResultsThe HFD resulted in elevated serum leptin and IL-6 in both mutants and controls, and reduced serum growth hormone (GH) and prolactin (PRL) levels. However, adrenocorticotropin (ACTH) levels were elevated in controls but not mutants. Unexpectedly, whereas controls gained as much weight as younger females, somatotrope LEPR-null mutants on a HFD gained only 75% of the weight of controls, were more glucose tolerant, consumed less food, were more active in the metabolic cages, and had lower serum levels of insulin. Analysis of scRNA-seq revealed that the HFD induced differentially expressed genes (DEGs) in more distinct pituitary cell populations of older mice compared to previously reported findings in younger control females, indicating greater vulnerability in the older pituitary population. This was especially true in the mutant pituitary population. Ingenuity Pathway Analysis indicated that the DEGs included targets of critical upstream regulators important for pituitary cell function and plasticity (CREB, Fox01, cAMP, STAT3, insulin, TRH, GnRH, and leptin signaling pathways), with most pathways predicted to be downregulated by the HFD. Unlike controls, HFD-fed mutant cell populations exhibited DEGs consistent with the downregulation of translational regulatory pathways. Notably, the HFD reversed the increased expression of progenitor cell markers (Sox9+) and multiple pituitary hormone transcripts seen in the mutant on a control diet. Similarly, the HFD also reversed the expression of multiple pituitary hormone transcripts and progenitor markers in lactotropes, thyrotropes, and corticotropes from mutants.ConclusionThe findings supported our hypothesis that both aging and the mutation (loss of LEPR in somatotropes) would render these mice more sensitive to a HFD as more pituitary cell types were affected transcriptionally. Collectively, these findings indicate that HFD and/or obese state may compromise pituitary plasticity by down-regulating translational processes and reducing expression in cells that may have multipotential functions. The oxidative stress of a HFD may thus limit the expression of pituitary progenitor cells.